Mild and metal-free trifluoromethylation and pentafluoroethylation of gem-difluoroalkenes with TMSCF3 and TMSCF2CF3. Issue 41 (14th October 2015) - Jin, Guanyi; Zhang, Xuxue; Fu, Dan; Dai, Wenpeng; Cao, Song
Abstract: A direct and efficient approach for the trifluoromethylation and pentafluoroethylation of 1, 1-diaryl-2, 2-difluoroethenes with TMSCF3 and TMSCF2 CF3 in the presence of TBAF was developed. The reactions proceeded smoothly under mild reaction conditions to give the corresponding monotrifluoromethylated, bistrifluoromethylated, monopentafluoroethylated and bispentafluoroethylated products in fair to good yields, respectively, without the addition of metal catalyst. Graphical abstract: